European cycling lexicon. Second edition: more languages, more terms, more information. - (:unkn) unknown (My University, 2010)
Das Fahrradlexikon übersetzt die Begriffe in 27 verschiedene Sprachen.
Keywords: Fahrradverkehr; Nachschlagewerk; Individualverkehr; Fahrradtechnik; Fahrradnutzung; Fahrradinfrastruktur; Fahrradtyp; Lexikon; Phrase